Pengaruh Psychological Capital, Motivasi Kerja dan Beban Kerja terhadap Kinerja Bintara Pelatih di Pusdikif Pussenif TNI AD - Putra Rizky Valeri; Nur Hayati (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2026)
This study aims to analyze the influence of Psychological Capital, work motivation, and workload on the performance of Training Officers at the Infantry Education Center (Pusdikif) of the Indonesian Army's Infantry Training Center (Pussenif. This study uses a quantitative approach with an explanatory survey design. The research population consists of all 60 non-commissioned officer trainers at Pusdikif Pussenif TNI AD. Data collection was conducted using a five-point Likert scale questionnaire. Data analysis was performed using multiple linear regression with the help of SPSS 29. The results show that Psychological Capital has no significant effect on the performance of non-commissioned officer trainers. Work motivation has a positive and significant effect on performance and is the most dominant variable. Workload has a positive and significant effect on performance. Simultaneously, Psychological Capital, work motivation, and workload have a significant effect on the performance of Training Officers. The research model has a very strong relationship (R = 0.856) with an explanatory power of 73.3%. This study shows that the performance of military trainers is more influenced by work motivation and task demands than by personal psychological factors. The results of this study are expected to serve as a basis for the leadership of the Indonesian Army's education units in increasing work motivation and managing the workload of trainers proportionally to support the improvement of military education performance.